INNOVATIVE CLUSTERING AS A STRATEGIC VECTOR FOR THE DEVELOPMENT OF THE AGRICULTURAL SECTOR OF THE LIBERATED TERRITORIES OF AZERBAIJAN - AHMADZADE, Jalal Vugar oglu (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article investigates the agricultural potential of the liberated territories of Azerbaijan (LAEO) and proposes strategic directions for clustering agriculture as a tool for sustainable rural development. In the context of global challenges such as demographic change and climate fluctuations, the study emphasizes that agricultural growth in the deoccupied regions requires not only land reforms but also the establishment of an innovative ecosystem supported by research centers, digital technologies, and public–private partnerships. Institutional transparency, a developed agro-technological infrastructure, and effective public policy are highlighted as crucial preconditions for long-term success. The research is grounded in the principle of objectivity, enabling the analysis of agricultural development as a complex socio-economic process. General scientific methods, including analysis and synthesis, comparison and analogy, and the processing of statistical data, were employed to identify the key factors influencing agricultural potential and strategic directions for clustering. The scientific novelty of this study lies in introducing a new strategic concept for the agricultural development of the liberated territories, shifting the focus from traditional small-scale farming to integrated agricultural clusters. These clusters are envisioned to combine large farms, research centers, innovation platforms, and institutional support. Drawing on the example of the Netherlands, the paper offers a comparative framework for establishing innovative agroecosystems in post-conflict zones. The study concludes that adjustments to existing legislation or the adoption of a new legal act on agricultural clustering are necessary. While the current agricultural policy—characterized by subsidies, tax incentives, loans, and simplified export procedures—is effective, it is insufficient to ensure global competitiveness. The state is therefore urged to assume a leading role in fostering partnerships between agribusiness, research institutions, universities, and venture financing. Following the European Union model, the creation of agricultural research centers in cities such as Aghdam and Fizuli is recommended, alongside the integration of advanced foreign technologies and the promotion of applied research. Special emphasis is also placed on state-supported training of agricultural specialists at Karabakh University to secure long-term sectoral development.